2021
DOI: 10.3389/fimmu.2021.679839
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony Stimulating Factor in Single Blastocyst Conditioned Medium as a Biomarker for Predicting Implantation Outcome of Embryo

Abstract: BackgroundIt is highly desirable to develop new strategies based on secretomics to more accurately selection of embryos with the highest developmental potential for transfer. Granulocyte-macrophage colony-stimulating factor (GM-CSF) has been reported to promote embryo development and pregnancy establishment. However, the predictive value of GM-CSF in single blastocyst selection remains unclear. This study is to determine the concentration of GM-CSF in human single-blastocyst conditioned medium (SBCM) and to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…41,43,102 Potential embryo-viability biomarkers in embryo secretome or embryo spent medium (E-SM), associated with improved IVF outcomes, reported so far include, sHLA-G, 49,50,83,86 microRNAs, 103 telomeric repeat-containing RNAs (TERRRA), 104 ubiquitin, 51,52,100 apolipoprotein-A, 105 platelet-activating factor (PAF), 106 human haptoglobin molecule, 107 human chorionic gonadotrophin (hCG), 108 mitochondria, 109 and mitochondrial DNA content, 110 Glutamine 53 and cytokines such as IL-1β, 72 tumour necrosis factor α (TNF-α), 72,111 LIF 111,112 and Granulocyte-macrophage colony stimulating factor (GM-CSF). 113 Among these identified embryo-derived biomolecules, sHLA-G and ubiquitin could be used as potential predictive biomarkers for improved LBR. They show a strong positive correlation with embryo developmental stage, their quality scores and LBR.…”
Section: Predictive Potential Of Embryo-derived Biomarkers and Their ...mentioning
confidence: 99%
See 3 more Smart Citations
“…41,43,102 Potential embryo-viability biomarkers in embryo secretome or embryo spent medium (E-SM), associated with improved IVF outcomes, reported so far include, sHLA-G, 49,50,83,86 microRNAs, 103 telomeric repeat-containing RNAs (TERRRA), 104 ubiquitin, 51,52,100 apolipoprotein-A, 105 platelet-activating factor (PAF), 106 human haptoglobin molecule, 107 human chorionic gonadotrophin (hCG), 108 mitochondria, 109 and mitochondrial DNA content, 110 Glutamine 53 and cytokines such as IL-1β, 72 tumour necrosis factor α (TNF-α), 72,111 LIF 111,112 and Granulocyte-macrophage colony stimulating factor (GM-CSF). 113 Among these identified embryo-derived biomolecules, sHLA-G and ubiquitin could be used as potential predictive biomarkers for improved LBR. They show a strong positive correlation with embryo developmental stage, their quality scores and LBR.…”
Section: Predictive Potential Of Embryo-derived Biomarkers and Their ...mentioning
confidence: 99%
“…51,52 Though, earlier studies on embryo biomarkers have showed their association with the embryo quality and pregnancy outcome. 49,50,53,72,83,86,89,113 they are still restricted on embryo viability biomarker estimations in E-SMs of morulae (day 4) and blastocyst stage (days 5-6), and their correlative analysis with pregnancy outcome in terms of LBR, following their ETs. Also, most studies so far have measured other biomarkers in only cleavage-stage embryos.…”
Section: Predictive Potential Of Embryo-derived Biomarkers and Their ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies focused on the secretion of immunological factors by human and murine embryos, as they play a major role in the embryo-maternal dialogue by facilitating immune-related implantation events (for review, see Bahrami-Asl [ 25 ]). Granulocyte–macrophage colony-stimulating factor, a pertinent regulator for the immune response during implantation, was detected in the secretome of both human [ 36 ] and murine [ 37 ] embryos, and was considered a potential marker of viable blastocysts [ 36 , 37 , 38 ]. Katz-Jaffe and colleagues [ 31 ] reported similar protein profiles between the human and murine secretome, and proposed the regulatory protein ubiquitin as a candidate biomarker for blastocyst development in both species [ 31 ].…”
Section: Introductionmentioning
confidence: 99%